2010
DOI: 10.1007/s00438-010-0588-6
|View full text |Cite
|
Sign up to set email alerts
|

hsf1+ extends chronological lifespan through Ecl1 family genes in fission yeast

Abstract: The heat shock factor (HSF), a protein evolutionarily conserved from yeasts to human, regulates the expression of a set of proteins called heat shock proteins (HSPs), many of which function as molecular chaperones. In Saccharomyces cerevisiae, the HSF binds to the 5' upstream region of YGR146C and activates its transcription. YGR146C encodes a functional homolog of ecl1 (+), ecl2 (+), and ecl3 (+) of Schizosaccharomyces pombe. At present, these Ecl1 family genes, which are extenders of chronological lifespan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Another aging-related protein, whose activity and content are critical for the cellular response to proteotoxic stresses, is Hsf1 [41]; [43]; [44]. When HSF1 is overexpressed from a plasmid in wild-type cells, we find attenuated aging-dependent aggregation of the mid-size 47Q and the long 103Q, as compared to cells expressing an empty plasmid (pRS314) instead of p HSF1 (Figure 5D).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Another aging-related protein, whose activity and content are critical for the cellular response to proteotoxic stresses, is Hsf1 [41]; [43]; [44]. When HSF1 is overexpressed from a plasmid in wild-type cells, we find attenuated aging-dependent aggregation of the mid-size 47Q and the long 103Q, as compared to cells expressing an empty plasmid (pRS314) instead of p HSF1 (Figure 5D).…”
Section: Resultsmentioning
confidence: 93%
“…In Caenorhabditis elegans , Hsf1 is required for enhanced thermotolerance and suppression of proteotoxicity and was also shown to regulate aging [41]; [42] and to affect lifespan extension by DR [43]. Hsf1 is a regulator of lifespan also in yeast, as the CLS extender Ecl2 in Schizosaccharomyces pombe and its functional homolog YGR146C in S. cerevisiae are direct targets of Hsf1 and overexpression of Hsf1 in fission yeast extends CLS [44]. Hsf1 is activated by heat-shock, oxidative, metabolic or environmental stresses, although our understanding of Hsf1 regulation remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that Ecl1 family genes are involved in chronological lifespan, H 2 O 2 resistance, and sexual development (Ohtsuka et al 2008(Ohtsuka et al , 2011. In this study, we newly identified the association between zinc or iron limitation-dependent sexual development and Ecl1 family proteins.…”
Section: Discussionmentioning
confidence: 80%
“…The open reading frame region of the Ecl1, Ecl2, and Ecl3 proteins was replaced with a kan R cassette to disrupt ecl1 + , ecl2 + , and ecl3 + individually and in combination, and the corresponding mutants JY333Δecl1, JY333Δecl2, JY333Δecl3, and JY333Δecl1Δecl2Δecl3 were prepared as described previously (Ohtsuka et al 2011). Using these strains, each h 90 strain and diploid strain were generated ( Table 1).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…6,7) ecl1 þ -mRNA is induced by nitrogen starvation and ecl2 þ -mRNA by heat shock, suggesting that Ecl1 family genes evolved to respond to different stressors and to survive under unfavorable conditions. 8,9) Ecl1 family genes appear to execute their functions primarily through the prr1 þ gene, which is a twocomponent system response regulator, and partially through the hsr1 þ gene, which encodes a zinc finger transcription factor similar to Msn2 of S. cerevisiae. 10,11) At present, Ecl1 family genes have been identified only in fungi, not in higher eukaryotes.…”
Section: )mentioning
confidence: 99%